Menjaga Warisan Bangsa: Upaya Perlindungan terhadap Tinggalan Megalitik di Kabupaten Sigi Sulawesi Tengah - Husain, Sarkawi B.; Rabani, La Ode; Haliadi, Haliadi; Rijal, Andi Syamsu (Jurnal Sejarah Citra Lekha, 2023)
Central Sulawesi is renowned for its abundance of vital megalithic remnants, with Poso and Sigi districts standing out as key areas with thousands of such remains. This article delves into the endeavors aimed at safeguarding these megalithic remnants, particularly those located in Sigi Regency, notably in Watunonju Village of Sigi Kota District and Loru Village of Sigi Bureaumaru District, commonly referred to as Watunonju. Many of the megalithic remnants preserved in these areas are stone mortars, locally known as "vatunonju". Preserving this invaluable heritage requires concerted protection efforts, including reinforcing customary laws that dictate fines for any damage inflicted upon the sites, elevating the status of these sites to a higher level, both provincially and nationally, and establishing and engaging a community dedicated to the conservation of megalithic remnants and other historical artifacts.